Physiological plasticity of metabolic rates in the invasive honey bee and an endemic Australian bee species - Tomlinson, S.; Dixon, Kingsley; Didham, R.; Bradshaw, S. (Springer Verlag, 2015)
Seasonal variation in metabolic rate and evaporative water loss as a function of ambient temperature were compared in two species of bees. The endemic blue-banded bee, Amegilla chlorocyanea, is a solitary species that is an important pollinator in the south-west Australian biodiversity hotspot. Responses were compared with the European honeybee, Apis mellifera, naturalised in Western Australia almost 200 years ago. Metabolic rate increased exponentially with temperature to a peak in both species, and then declined rapidly, with unique scaling exponents and peaks for all species-by-season comparisons. Early in the austral summer, Apis was less thermally tolerant than Amegilla, but the positions reversed later in the foraging season. There were also significant exponential increases in evaporative water loss with increasing temperature, and both season and species contributed to significantly different responses. Apis maintained relatively consistent thermal performance of metabolic rate between seasons, but at the expense of increased rates of evaporative water loss later in summer. In contrast, Amegilla had dramatically increased metabolic requirements later in summer, but maintained consistent thermal performance of evaporative water loss. Although both species acclimated to higher thermal tolerance, the physiological strategies underpinning the acclimation differed. These findings may have important implications for understanding the responses of these and other pollinators to changing environments and for their conservation management.